2016
DOI: 10.1016/j.jaap.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microbial biomass in subseafloor sediment by pyrolysis⿿GC/MS

Abstract: The conventional approaches for qualitative and quantitative assessment of microbial biomass in sediments, e.g. via quantitative polymerase chain reaction or intact polar lipids analysis, are rather tedious and time-consuming. Here we present a new, optimized and simple pyrolysis-gas chromatography/mass spectrometry protocol for rapid screening of sediment samples for the presence of microbial signals and quantification of bulk population.Analysis of microbial cultures of different bacterial and archaeal linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It is possible that this method could be used to expand examination of accumulated biological factors; Py-GCMS has been used to this end previously. Zhu, et al [67] used Py-GCMS to quantify microbial biomass through the detection of specific "microbial signals"…”
Section: Chromatography-mass Spectrometrymentioning
confidence: 99%
“…It is possible that this method could be used to expand examination of accumulated biological factors; Py-GCMS has been used to this end previously. Zhu, et al [67] used Py-GCMS to quantify microbial biomass through the detection of specific "microbial signals"…”
Section: Chromatography-mass Spectrometrymentioning
confidence: 99%
“…(2018) who found fungal gene expression associated with secretion of exoenzymes that break complex refractory compounds in marine sediments. Although necromass is thought to be a limited source of energy for microbial communities in marine sediments (Bradley et al ., 2018), other studies suggest necromass is a non‐trivial source of carbon and energy in deep subsurface habitats (Lomstein et al ., 2012; Jørgensen and Marshall, 2016; Zhu et al ., 2016; Braun et al ., 2017; Thomas et al ., 2019). Fungi can thus be seen as able to potentially recycle ‘their own’ or their dead neighbours in a cannibalistic way (Zinke et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since organic matter degradation is intensive in surficial sediment layers (Orcutt et al ., 2011b), deeper subsurface microbes may depend on pools of remaining refractory organic matter, necromass and delivery of nutrients by subsurface fluid flows (Jørgensen and Marshall, 2016). It was recently reported that deep subsurface allochtonous and autochtonous necromass may provide some fraction of the energy needs of deep biosphere microorganisms (Zhu et al ., 2016; Bradley et al ., 2018). Despite expected challenges for obtaining sufficient carbon and energy in this lithified realm, microbial chemoheterotrophs, including fungi, can survive.…”
Section: Introductionmentioning
confidence: 99%
“…Other microbial pyrolysis products selected for tracking microbial signals, this case in sediments, are Benzyl nitrile, 2-furanmethanol, indole, phenol and pyrrole (Zhu et al 2016). In the present study, phenol and Indole were clearly discernible in all chromatograms.…”
Section: Figmentioning
confidence: 99%
“…Pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) has been widely applied for the study of complex materials such as soil organic matter and recently for biomass characterisation (Liu et al 2016;Zhu et al 2016). The main advantages of the pyrolysis route for analysing complex organic samples are minimal sample preparation, minimum time of analysis and relative low cost (Prasad et al 2006).…”
Section: Introductionmentioning
confidence: 99%